Soil fertility under different nitrogen irrigation methods in potato (Solanum tuberosum) - SHRI MAAN, DEVA; KUMAR, AMIT; SINGH, DAVINDER; DUHAN, ANSUL (The Indian Journal of Agricultural Sciences, 2022)
A field experiment was conducted during rabi 2015–16 and 2016–17 to assess influence of nitrogen levels and irrigation methods on soil nutrients under potato cultivation at Hisar, Haryana. The treatments comprising of irrigation methods (drip and furrow) and five doses of nitrogen (60, 80, 100, 120 and 140% of RDN) were laid out in split plot design replicated thrice. Among nitrogen levels, the mean maximum available soil nitrogen (N) was recorded in 60% of RDN (121.00; 124.00 kg/ha) during 2015–16 and 2016–17, respectively. With respect to irrigation methods, the mean maximum available soil N was recorded under drip irrigation (113.73; 112.87 kg/ha) 2015–16 and 2016–17,respectively. Considering the available soil phosphorous during 2015–16, minimum was recorded in the treatment 100% of RDN (10.34 kg/ha) and maximum was recorded in 60% of RDN (20.50 kg/ha). The interaction effect of irrigation method at same level of RDN and of RDN at same irrigation method was found significant for soil nutrients. The minimum available soil N (104.67 kg/ha) and P (8.00 kg/ha) were obtained with drip irrigation at 100% RDN during 2015–16. Similar interaction effects were observed regarding available N and P during 2016–17. Hence, 100% of RDN with drip irrigation condition proved the best treatment.